GANGGUAN SENSORY INTEGRASI PADA ANAK DENGAN AUTISM SPECTRUM DISORDER - MUCHAMAD IRVAN (Buana Pendidikan, 2017)
Autism Spectrum Disorder is a complex developmental disorder, indicated by symptoms of social communicationdisorders, social interactiondisorders, repetitive and restricted behavior disorders whose development is already visible at the age of 3 years. Repetitive behavior disorder is performed by children with ASD throughout the day that it interferes with progress in carrying out social activities. The restricted behavioral disorders are impaire in the behavior of interest, according to age, in which children with ASD showed interest in an object or activity is improper. Behavioral disorders experienced by children with ASD occurs because of the misperception, in which the sensory input is not integrated, properly can result in a child with ASD interpreting the world differently. The more behavioral disorders caused by inaccuracy in sensory processing systems integration. As for sensory integration disorder that can be experienced by children with ASD are three types of Sensory Modulation Disorder (SMD), Sensory-Based Motor Disorder (SBMD), Sensory Discrimination Disorder (SDD).